Rethinking Biosafety in Research on Potential Pandemic Pathogens - Marc Lipsitch (American Society for Microbiology, 2012)
ABSTRACT If accidentally released, mammalian-transmissible influenza A/H5N1 viruses could pose a greater threat to public health than possibly any other infectious agent currently under study in laboratories, because of such viruses’ likely combination of transmissibility and virulence to humans. We advocate explicit risk-benefit assessments before work on such pathogens is permitted or funded, improvement of biosafety practices and enforcement, and harmonization of criteria for permitting such experiments across government agencies, as well as internationally. Such potential pandemic pathogens, as they have been called, jeopardize not only laboratory workers and their contacts, but also the wider population, who should be involved in assessments of when such risks are acceptable in the service of scientific knowledge that may itself bear major public health benefits.